Denervation procedure of the lateral epicondyle for refractory lateral epicondylitis - Misty Suri, MD, MS; Arjun Verma, BS; Collyn O’Quin, MD; Gregory Parker, MD; Kareem Mohamed, MD; Hunter Starring, MD; Daniel Yoo, MD (JSES International)
Background: Lateral epicondylitis is the most common cause of lateral elbow pain in adults, and nonoperative treatment is the first-line management modality of choice. Pain refractory to conservative management may improve with surgical interventions involving extensor carpi radialis brevis débridement or denervation. This investigation was conducted to evaluate the long-term analgesic efficacy, incidence of postoperative sensory deficits, and postoperative elbow functionality in patients who underwent a denervation surgery of the posterior branch of the posterior cutaneous nerve of the forearm (PBPCNF) for refractory lateral epicondylitis. Methods: This investigation was an institutional review board–approved, single-center, single-surgeon case series of 22 patients who underwent denervation surgery with an average final follow-up of 4.7 years. Inclusion criteria for surgery were a minimum of 6 months symptom duration refractory to conservative therapies, a minimum of 2 years clinical follow-up, and significant (70-80%) pain relief from the nerve block test. Visual Analog Scale pain and Single Assessment Numeric Evaluation scores were used to assess pain and function, respectively. The incidence of postoperative sensory deficits was evaluated via clinical exam. Results: Compared to the preoperative average, the cohort’s mean Visual Analog Scale pain was significantly decreased at all postoperative follow-up intervals, including 2 weeks, 1 year, and final average follow-up of 4.7 years. At the final follow-up, the mean Single Assessment Numeric Evaluation score was 98.8 ± 2.6, and one patient (4.5%), who reported the same sensory deficit preoperatively, reported postoperative sensory deficits. Conclusion: The PBPCNF denervation procedure is a highly efficacious procedure for achieving long-term pain control in the treatment of refractory lateral epicondylitis. The PBPCNF denervation procedure affords patients a high level of postoperative functionality with a low incidence of sensory deficits.